Effective School Management in Implementing the Pancasila Student Profile Strengthening Project at SMA Negeri 15 Palembang - Desniyanti, Desniyanti; Lian, Bukman; Nugroho, Heri Setiyo (PPSDP International Journal of Education, 2025)
This study aims to examine school management in implementing the Projek Penguatan Profil Pelajar Pancasila (P5) at SMA Negeri 15 Palembang, focusing on planning, organizing, implementing, and supervising P5 activities. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. The findings indicate that effective school management is crucial for successful P5 implementation, involving collaborative planning, structured team formation, contextual project-based learning, and regular monitoring and evaluation. Key success factors include strong school leadership, active teacher and student participation, and a supportive school environment. This study provides empirical insights into how school management strategies facilitate the P5 program within the Merdeka Curriculum framework, emphasizing the integration of Pancasila values in student character development. The research offers actionable recommendations for school administrators and policymakers to enhance P5 implementation through structured management practices, stakeholder engagement, and continuous evaluation. This study contributes to the literature on educational management by highlighting best practices in implementing character-based projects, supporting the broader goals of Indonesia’s Merdeka Curriculum.